Conducta Obstétrica en multípara de 35 años de edad con hemorragia postparto - Arreaga Sellan, Evelyn Gabriela (2021)
Postpartum hemorrhage is one of the most important obstetric emergencies, being one of the main causes of admission to hospital units for patients with a pregnancy and recent postpartum women. It is one of the three leading causes of maternal mortality in the world, especially in developing countries. Postpartum hemorrhage can be prevented through the correct management of the third stage of labor (MATEP), which consists of a series of components: such as uterotonic use such as oxytocin, correct traction and contratraction of the umbilical cord and the uterine massages. A clinical case of a 35-year-old patient is presented who is admitted to the emergency area of the Martin Icaza hospital for a segmental cesarean section, the patient presents an emergency of postpartum hemorrhage, the red key is activated and acts are performed according to the protocols, later She presented an alteration in her vital signs developing eclampsia and was referred to the third level of hospital care. The purpose of the elaboration of this clinical case is to be able to make known the importance of the correct management of Postpartum Hemorrhage, additionally it is intended to indicate the importance of recognizing the alarm signs in each prenatal control.